Factors inhibiting the promotion of civil servants at the department of education in Mimika Regency - Karapa, Naomi; Marlissa, Elsyan R.; Urip, Transna Putra (Goodwood Publishing, 2025)
Purpose: This study aims to identify and analyze the factors inhibiting the promotion of civil servants at the Department of Education in Mimika Regency, focusing on structural, bureaucratic, and non-technical barriers that affect fairness and effectiveness.Design/methodology/approach: Research/methodology: A mixed-methods approach was used, combining quantitative data (descriptive and inferential statistics such as Pearson correlation and ANOVA) with qualitative insights from semi-structured interviews and focus group discussions (FGDs). The study involved 74 civil servants selected from a population of 91 using Slovin’s formula, with triangulation applied to ensure the data validity. Results: The findings show that complex bureaucracy, unclear implementation of promotion policies, and weak dissemination are key structural barriers. Non-technical factors, including favoritism, interpersonal relations, and internal politics, also significantly influenced promotion outcomes. Competence alone proved insufficient, as subjective judgments and limited access to training opportunities also affected the results. Conclusions: Promotions in the Mimika Education Office are hindered by bureaucratic complexity, unclear policies, and non-technical factors such as favoritism and politics. Competence is insufficient, as limited training access and unequal opportunities persist. A transparent, merit-based system is essential for improving fairness, motivation, and organizational performance. Limitations: This study was limited by its focus on a single office, which may not represent other institutions. Incomplete budgetary data also constrain financial analyses. Contribution: This research enriches public sector HR studies by showing how bureaucracy and sociocultural dynamics intersect in career development, offering policy input for transparent, merit-based promotion and competency development in remote regions such as Mimika.